Os direitos da personalidade e as liberdades públicas: uma relação simbiótica visando à proteção da pessoa - Roberto Brandão Federman Saldanha (2011)
The interactions between "Personality Rights" and "Civil Liberties" have been established in the context of new hermeneutic standards conceived in the Democratic Rule-of-Law State. The present work intends to demonstrate the connection between those institutes that have been developed in similar historical and philosophical contexts. Primarily civil liberties and the personality rights will be analyzed individually, to allow, at a later stage, the understanding of both concepts as inseparable elements in the completeness of the legal system. The scarcity of previous academic studies on this theme has commonly privileged certain insufficient notions that lack the technical rigour indispensable to interdisciplinary analyses. The present work will provide a methodologically correct interpretation of the modern theories concerning the fundamental rights in order to delineate the theme. The above mentioned interconnection will be addressed through the analysis of the modern legal principles – such as the right to free development of personality –and by means of the examination of specific rights that can be categorized concomitantly as a personality right and a civil liberty – for example, the right to private life.